The Demise of Poskanzer and Schwab’s Influenza Theory on the Pathogenesis of Parkinson’s Disease - Danny Estupinan; Sunina Nathoo; Michael S. Okun (Parkinson's Disease)
In 1961, David C. Poskanzer and Robert S. Schwab presented a paper, “Studies in the epidemiology of Parkinson’s disease predicting its disappearance as a major clinical entity by 1980.” This paper introduced the hypothesis that Parkinson’s disease was derived from a single aetiology, the influenza virus. We review the original Poskanzer and Schwab hypothesis that Parkinson’s disease was based on the association between the 1918-19 influenza epidemic and the later observation of Parkinsonism in some influenza sufferers. We also further explore the prediction that Parkinson’s disease would totally disappear as an entity once original influenza victims were all deceased. Current research has revealed that there are many potential causes and factors important in the occurrence of Parkinson’s disease, postencephalitic Parkinsonism, and encephalitis lethargica. Poskanzer and Schwab presented a novel hypothesis; however, it was proven false by a combination of research and time.